2021
DOI: 10.3390/s21134595
|View full text |Cite
|
Sign up to set email alerts
|

UAV Path Planning for Reconnaissance and Look-Ahead Coverage Support for Mobile Ground Vehicles

Abstract: Path planning of unmanned aerial vehicles (UAVs) for reconnaissance and look-ahead coverage support for mobile ground vehicles (MGVs) is a challenging task due to many unknowns being imposed by the MGVs’ variable velocity profiles, change in heading, and structural differences between the ground and air environments. Few path planning techniques have been reported in the literature for multirotor UAVs that autonomously follow and support MGVs in reconnaissance missions. These techniques formulate the path plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In such a scenario, the UAV cannot provide continuous and adequate visual support while following the GMT. Existing path planning, such as G-APFs [24], ED-APFs [25], and D-APFs [12], lack the ability to handle wind effects and thus cannot be used in real-world applications because the realistic environment is amorphous and windy. The proposed path-planning technique solves this problem by modifying the attractive force of the D-APF and ED-APF to enhance the sensitivity and by introducing a standoff distance based on the roll and pitch angles which are sensitive to wind speed and direction and to UAV speed.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…In such a scenario, the UAV cannot provide continuous and adequate visual support while following the GMT. Existing path planning, such as G-APFs [24], ED-APFs [25], and D-APFs [12], lack the ability to handle wind effects and thus cannot be used in real-world applications because the realistic environment is amorphous and windy. The proposed path-planning technique solves this problem by modifying the attractive force of the D-APF and ED-APF to enhance the sensitivity and by introducing a standoff distance based on the roll and pitch angles which are sensitive to wind speed and direction and to UAV speed.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Nevertheless, several existing solutions have tried utilizing SDN or a multi-objective routing for ground vehicles [ 10 , 11 , 12 ]. Moreover, routing in UAVs which considers metrics such as charging stations, VANET supporting networks, and trajectory-based systems has also been proposed [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. An exhaustive review of existing schemes identified that a routing scheme should not consider a single objective while disregarding its byproduct’s impact.…”
Section: Introductionmentioning
confidence: 99%
“…Unmanned aerial vehicles (UAVs) have attracted increasing attention in recent years for their wide range of applications, including pesticide spraying [1], aerial photography [2], environmental monitoring [3], reconnaissance [4], and transportation [5]. In addition to these non-contact tasks, there are increasing demands on contact-based operations such as industrial contact inspection [6], window-cleaning [7], peg-in-hole assembly [8], and aerial grasping [9].…”
Section: Introductionmentioning
confidence: 99%